Toxocariasis: an epidemiological contribution from the Feira area - Tavares, Luís P.; Garrido, Jorge; Geraldes, Carlos A.; Tavares, Maria C.; Faria, Ana C. (Portuguese Journal Internal Medicine, 1998)
Toxocariasis and visceral larva migrans are clinical entities underdiagnosed, because of deficient knowledge in the medical class, and other health technicians concerning parasitic infections. ln Portugal, recent prospective studies show that the prevalence rates of Toxocaracanis infection in dogs, humans & contamination of soil infection, are alarming. The present study, sampled 513 persons who live in Feira district. A 17, 7% seropositivity level was found. The authors statistically analysed the data by sex, age, occupation, residence, clinicai and laboratorial signs, dog posession and type of exposure. Seropositive individuais were treated with me bendazole or albendazole on a randomly selected basis.